2019
DOI: 10.1111/anec.12623
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel exon3 deletion of RYR2 in a family with catecholaminergic polymorphic ventricular tachycardia

Abstract: Background RYR2, encoding cardiac ryanodine receptor, is the major responsible gene for catecholaminergic polymorphic ventricular tachycardia (CPVT). Meanwhile, KCNJ2, encoding inward‐rectifier potassium channel (IK1), can be the responsible gene for atypical CPVT. We recently encountered a family with CPVT and sought to identify a responsible gene variant.MethodsA targeted panel sequencing (TPS) was employed in the proband. Copy number variation (CNV) in RYR2 was identified by focusing on read numbers in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Interestingly, the NTD harbors a number of RyR2 mutations associated with cardiomyopathies. (16,21,(27)(28)(29)(30)(31)(32)(33). A common defect of NTD RyR2 mutations is a reduced threshold for Ca 2+ release termination and an increased amplitude of fractional Ca 2+ release (34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the NTD harbors a number of RyR2 mutations associated with cardiomyopathies. (16,21,(27)(28)(29)(30)(31)(32)(33). A common defect of NTD RyR2 mutations is a reduced threshold for Ca 2+ release termination and an increased amplitude of fractional Ca 2+ release (34).…”
Section: Introductionmentioning
confidence: 99%
“…The NTD (residues 1–642) comprises three subdomains: NTD-A, NTD-B, and NTD-C. We showed that NTD-A is important for Ca 2+ release termination, NTD-B is involved in channel suppression, and NTD-C is critical for channel activation and expression ( 26 ). Interestingly, the NTD harbors a number of RyR2 mutations associated with cardiomyopathies ( 16 , 21 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ). A common defect of NTD RyR2 mutations is a reduced threshold for Ca 2+ release termination and an increased amplitude of fractional Ca 2+ release ( 34 ).…”
mentioning
confidence: 99%
“…Mutations in the RYR2 gene have been linked to cardiac arrhythmias (eg, CPVT and CRDS) [4][5][6][7][8]16 and cardiomyopathies such as left ventricular noncompaction (LVNC). 6,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] The mechanisms underlying RyR2-associated cardiac arrhythmias have been extensively studied. 7,16 However, the underlying mechanism for RyR2-associated LVNC remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[17][18][19][20][21][22][23] For instance, several unrelated families with an in-frame deletion of exon-3 in the RYR2 gene presented with an expanding spectrum of phenotypes, including left ventricular noncompaction cardiomyopathy (LVNC) as well as CPVT. 6,[24][25][26][27][28][29][30] In vitro functional characterization revealed that the exon-3 deletion reduced the threshold for store overload-induced spontaneous Ca 2+ release, 31 which may account for the increased propensity for stress-induced ventricular arrhythmias (VAs; ie, CPVT). Interestingly, the exon-3 deletion also markedly reduced the threshold at which spontaneous Ca 2+ release terminates.…”
Section: Novelty and Significancementioning
confidence: 99%
“…CPVT is also commonly induced by RYR2 variants and has been highly associated with bradycardia ( Miyata et al, 2018 ). An exon 3 deletion of RYR2 (c.169-353_273 + 657del) was found in a family with a history of SND and CPVT ( Dharmawan et al, 2019 ). Exon 3 deletions were identified in two additional families that showed symptoms of SND ( Bhuiyan et al, 2007 ).…”
Section: Genetics Of Sinoatrial Node Dysfunctionmentioning
confidence: 99%